Epidemiological Study of Mycobacterium bovis Infection in Buffalo and Cattle in Amazonas, Brazil - Carneiro, Paulo A. M.; Takatani, Haruo; Pasquatti, Taynara N.; Silva, Christian B. D. G.; Norby, Bo; Wilkins, Melinda J.; Zumárraga, Martín José; Araujo, Flabio R.; Kaneene, John B. (Frontiers in Veterinary Science, 2019)
Bovine Tuberculosis (BTB) is an endemic disease in about one hundred countries, affecting the economy causing a decrease in productivity, condemnation of meat, and damaging the credibility on international trade. Additionally, Mycobacterium bovis the major causative agent for BTB can also infect humans causing a variety of clinical presentations. The aim of this study was to determine BTB prevalence and the main risk factors for the Mycobacterium bovis infection in cattle and buffalos in Amazonas State, Brazil. Tissue samples from 151 animals (45 buffalo and 106 cattle) were obtained from slaughterhouses under State Veterinary Inspection. M bovis were isolated on Stonebrink medium. The positive cultures were confirmed by polymerase chain reaction testing. The apparent herd and animal prevalence rates were 40.54% and 5.40%, respectively. Regarding animal species, the apparent prevalence rates were 1.26% in cattle and 9.41% in buffalo. Generalized Linear Mixed Models (GLMM) with random effect were used to assess the association with risk factors on the prevalence. Species (buffalo), herds size (>100 animals) and the presence of both species (buffalo and cattle) in the herd were the major risk factors for the infection by Mycobacterium bovis in the region. The findings reveal an urgent need for evidence-based effective intervention to reduce BTB prevalence in cattle and buffalo and prevent its spread to the human population. Studies are needed to understand why buffalo are more likely to be infected by M. bovis than cattle in Amazon. Recommendations for tuberculin skin testing prior to animal movement, inspection services being more alert during inspection of buffalo products, special attention for BTB status in herds over 100 animals, and discouragement of practices that promote the mixing of cattle and buffalo, were made.